2010
DOI: 10.1590/s1135-57272010000600009
|View full text |Cite
|
Sign up to set email alerts
|

Factores sociodemográficos y de salud asociados a la institucionalización de personas dependientes

Abstract: RESUMENFundamento: El análisis del efecto que diferentes variables tie nen en la institucionalización de las personas dependientes es un tema escasamente estudiado en España. El objetivo del trabajo es analizar qué factores sociodemográficos y del estado de salud pue den influir en la probabilidad de que la persona dependiente viva en una residencia.Métodos: Se realizó un estudio transversal de la población dependiente de la provincia de Cuenca, a partir de una muestra repre sentativa de la población baremada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
1
0
0
1
Order By: Relevance
“…When referring to the level of education of the subjects, the results of this research are similar to those found by other researchs (26) , where a large percentage of the residents present a low level of education. Regarding origin, the majority of the residents come from urban backgrounds, and here the percentage of men is higher, being men who live alone.…”
Section: Rev Esc Enfermsupporting
confidence: 90%
“…When referring to the level of education of the subjects, the results of this research are similar to those found by other researchs (26) , where a large percentage of the residents present a low level of education. Regarding origin, the majority of the residents come from urban backgrounds, and here the percentage of men is higher, being men who live alone.…”
Section: Rev Esc Enfermsupporting
confidence: 90%
“…Leturia (1999) afirma que, durant anys, la literatura científica només s'ha centrat en els efectes negatius que comporta la institucionalització; i és a partir dels anys 90, que es comencen a visibilitzar els primers estudis en què aquests efectes es positivitzen coincidint amb els canvis de model assistencial i d'atenció a les persones dependents(Ayuso, Pozo i Escribano, 2010;Gaugler, Duval, Anderson i Kane, 2007; IMSERSO, 2006).…”
unclassified